Acid‐Functionalized Mesoporous Carbon: An Efficient Support for Ruthenium‐Catalyzed γ‐Valerolactone Production. Issue 15 (18th June 2015) - Villa, Alberto; Schiavoni, Marco; Chan‐Thaw, Carine E.; Fulvio, Pasquale F.; Mayes, Richard T.; Dai, Sheng; More, Karren L.; Veith, Gabriel M.; Prati, Laura
Abstract The hydrogenation of levulinic acid has been studied using Ru supported on ordered mesoporous carbons (OMCs) prepared by soft‐templating. P‐ and S‐containing acid groups were introduced by postsynthetic functionalization before the addition of 1 % Ru by incipient wetness impregnation. These functionalities and the reaction conditions mediate the activity and selectivity of the levulinic acid hydrogenation. The presence of S‐containing groups (Ru/OMC‐S and Ru/OMC‐P/S) deactivates the Ru catalysts strongly, whereas the presence of P‐containing groups (Ru/OMC‐P) enhances the activity compared to that of pristine Ru/OMC. Under mild conditions (70 °C and 7 bar H2) the catalyst shows high selectivity to γ‐valerolactone (GVL; >95 %) and high stability on recycling. However, under more severe conditions (200 °C and p<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2f0rbbgt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> H 2</alternatives>=40 bar) Ru/OMC‐P is particularly able to promote GVL ring‐opening and the consecutive hydrogenation to pentanoic acid.